Risk-adjusted mortality in severely injured adult trauma patients in Sweden. Issue 2 (6th April 2022) - Strömmer, Lovisa; Lundgren, Fredrik; Ghorbani, Poya; Troëng, Thomas
Abstract: Background: Risk-adjusted mortality (RAM) analysis and comparisons of clinically relevant subsets of trauma patients allow hospitals to assess performance in different processes of care. The aim of the study was to develop a RAM model and compare RAM ratio (RAMR) in subsets of severely injured adult patients treated in university hospitals (UHs) and emergency hospitals (EHs) in Sweden. Methods: This was a retrospective study of the Swedish trauma registry data (2013 to 2017) comparing RAMR in patients (aged 15 years or older and New Injury Severity Score (NISS) of more than 15) in the total population (TP) and in multisystem blunt (MB), truncal penetrating (PEN), and severe traumatic brain injury (STBI) subsets treated in UHs and EHs. The RAM model included the variables age, NISS, ASA Physical Status Classification System Score, and physiology on arrival. Results: In total, 6690 patients were included in the study (4485 from UHs and 2205 from EHs). The logistic regression model showed a good fit. RAMR was 4.0, 3.8, 7.4, and 8.5 percentage points lower in UH versus EH for TP ( P  < 0.001), MB ( P  < 0.001), PEN ( P  = 0.096), and STBI ( P  = 0.005), respectively. The TP and MB subsets were subgrouped in with (+) and without (−) traumatic brain injury (TBI). RAMR was 7.5 and 7.0, respectively, percentage points lower in UHs than in EHs in TP + TBI and MB + TBI (both P  < 0.001). In the TP–TBI ( P  = 0.027) and MB–TBI ( P  = 0.107) subsets the RAMR was 1.6 and 1.8 percentage points lower, respectively. Conclusion: The lower RAMR in UHs versus EH were due to differences in TBI-related mortality. No evidence supported that Swedish EHs provide inferior quality of care for trauma patients without TBI or for patients with penetrating injuries. Abstract : A population-based trauma register was used to develop a risk-adjustment model in order to compare mortality between university and emergency hospitals in clinically relevant subsets of trauma patients (multiple blunt trauma, penetrating truncal trauma, and severe traumatic brain injury). The results suggest that university hospitals outperform emergency hospitals when it comes to the treatment of traumatic brain injury, but the differences in outcome following extracranial trauma appear more uniform. We recommend monitoring of risk-adjusted mortality in clinically relevant subsets for the continuous evaluation of quality of trauma care.